Modern TRIZ modeling in master programs : introduction to TRIZ basics at university and industry - Orloff, Michael A. (Springer, 2020)
The book is addressed to Master-students, senior students of universities, professors working at Master Programs, as well as researchers, engineers and managers of all industries without restrictions. Examples and illustrations of the book give a vivid impression of the spectrum of creative models of Modern TRIZ, which can be opened in any design and managerial decisions. The book is especially useful for students for performing TRIZ modeling and for inventing original ideas at Master Programs. The book is indispensable for passing Master Programs led by the author at the MTRIZ Academy.